Development and validation of recipes using consumers’ terms obtained through the application of the Think Aloud technique - Lezama Solano, Adriana (Kansas State University, 2018)
Cooking is part of almost everyone’s daily life. During cooking, recipes are usually used as a guide for home cooks to help them take decisions and get a tasty and appealing food product. Recipes have a great impact on consumers’ behavior and decision making at the kitchen. However, building a recipe requires understanding of the potential user, including explaining to him/her, in layman’s terms, the best way to prepare the food product. Nevertheless, what is the best way to communicate to consumers through a recipe? A qualitative sensory technique that allows collecting data regarding people’s motivations and actions during cooking is required in order to retrieve this information. The technique needs to allow data collection about the motivations, and the actions inspired by these. Recipes can use these motivations and actions to communicate to recipe users. This research proposes the use of the Think Aloud method, a technique that has not been used on sensory research, as a technique that can meet these goals. The objective of this study was to develop and evaluate different recipe styles for the preparation of doughs by understanding and using people’s descriptions, techniques and preparation terms through the application of the Think Aloud technique. Two qualitative studies were performed with wheat dough preparers (n=43) recruited in Manhattan, KS and corn dough preparers (n=50) recruited in Guadalupe, Costa Rica. During the interviews, participants verbalized the process of preparing the doughs, as well as their decision-making process through the Think Aloud technique. Results showed that participants provided enough data by thinking aloud. It was observed that the use of the Think Aloud method allowed them to be aware of texture characteristics in the dough. The ready doughs were mainly described as not sticky, soft and pliable. The most common techniques used to make the doughs included stirring, pushing/pressing/squeezing, and incorporate all together. Five recipes were written based on these descriptions. Three of the recipes included a step-by-step numbered format with a different amount of detail: not detailed, very detailed, and detailed recipe. The other two formats, both based on the detailed recipe, included a paragraph form recipe and a recipe with images. Wheat and corn recipes were validated in two online surveys (per study, n=300) where respondents evaluated the easiness, likeability, likelihood of using the recipe, helpfulness of the format, and amount of information. Overall, respondents considered the recipe with images easier and more helpful. The very detailed recipe was considered more difficult, less helpful and was liked less than the other recipes. Understanding and identifying the words and techniques people use at the kitchen represent a useful tool that can be used to communicate to other preparers how to make a food product. The Think Aloud technique represents a useful technique to collect information regarding consumers’ actions and motivations. The data collected through the application of the technique allowed building different recipe styles to communicate to consumers how to prepare a food product.
Keywords: Dough; Recipes; Think Aloud technique; Qualitative sensory research; Consumers' terms